Environmental Contamination during Influenza A Virus (H5N1) Outbreaks, Cambodia, 2006 - Vong, Sirenda; Ly, Sowath; Mardy, Sek; Holl, Davun; Buchy, Philippe (Emerging infectious diseases, 2008)
To determine potential risk for bird-to-human transmission during influenza A virus (H5N1) outbreaks among backyard poultry in rural Cambodia, we collected environmental specimens. Viral RNA was detected in 27 (35%) of 77 specimens of mud, pond water, water plants, and soil swabs. Our results underscore the need for regular disinfection of poultry areas.